2022
DOI: 10.1177/15280837211056987
|View full text |Cite
|
Sign up to set email alerts
|

Stab resistance of flexible composite reinforced with warp-knitted fabric like scale structure at quasi-static loading

Abstract: The stab-resistant fabric like scale structure has a promising application prospect for areas of stab prevention owing to its great flexibility and excellent stab-resistance performance. In this paper, a kind of novel stab-resistant fabric has been designed by coating with epoxy resin (ER) and silicon carbide (SiC) particles, which was based on the warp-knitted fabric like scale structure (WKFS). The uniformity of dispersion has been investigated with different diameter and mass fraction of SiC, and polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In addition, the protective properties of textiles can also be significantly improved by adjusting the type, [28] content, [29] particle size, [30] orientation and distribution, [31] and other parameters of the nanofillers. [32][33][34][35] Although such coatings have many advantages for the target application, we discovered that using a continuous coating to cover a textile negatively impacts its flexibility and breathability. As a result, it is still challenging to simultaneously improve the protective performance of personal protective equipment while maintaining its original flexibility and breathability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the protective properties of textiles can also be significantly improved by adjusting the type, [28] content, [29] particle size, [30] orientation and distribution, [31] and other parameters of the nanofillers. [32][33][34][35] Although such coatings have many advantages for the target application, we discovered that using a continuous coating to cover a textile negatively impacts its flexibility and breathability. As a result, it is still challenging to simultaneously improve the protective performance of personal protective equipment while maintaining its original flexibility and breathability.…”
Section: Introductionmentioning
confidence: 99%
“…A warp-knitted scale structure was prepared in the same lab, in this case using epoxy resin with SiC particles to impregnate the scales [ 39 ]. They reported an increase in the stab resistance due to the addition of SiC particles, but also mention that the knitted material (here polyester and Spandex) should be changed to a technical yarn, and washing of the composite structure should be tested.…”
Section: New Shapes and Polymersmentioning
confidence: 99%
“…Previous studies have indicated that yarn slip is the primary factor causing cutting or puncture failure of original high-performance ber textiles, and nowadays, coating is one of the most advanced strategies, including shear thickening uid (STF) [27][28][29][30], hydrogel [31][32][33][34], exible resin [2,35,36] and hard particle [37,38]. For instance, Liu [39] designed a new type of stab-resistant fabric based on the warp knitted scale structure by coating epoxy resin reinforced by inorganic powder (Epoxy/IP). Fan [27] treated the fabric with nano-SiO 2 /shear thickening gel (STG), which greatly increased the peak piercing force of the STG-treated fabrics in puncture testing compared to neat samples.…”
Section: Introductionmentioning
confidence: 99%